2015
DOI: 10.1242/jcs.163683
|View full text |Cite
|
Sign up to set email alerts
|

Basolateral secretion of Wnt5a in polarized epithelial cells is required for apical lumen formation

Abstract: BSTRACTWnt5a regulates planar cell polarity in epithelial cells, but it remains to be determined whether Wnt5a and its receptors are sorted apically or basolaterally, and how Wnt5a signaling is involved in apical and basolateral polarization. We found that Wnt5a was secreted basolaterally in polarized kidney epithelial cells. The basolateral secretion of Wnt5a required Wntless (Wls), clathrin and adaptor protein 1 (AP-1). Wnt5a receptors were also localized to the basolateral membranes, but their sorting did n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 55 publications
2
23
0
Order By: Relevance
“…WNT5A is a complex protein that not only has multiple isoforms, but that also undergoes many PTMs that dictate its cellular effects through interactions with different receptors . Our study validates and adds to the complexity of WNT5A by identifying a unique, posttranslational phosphorylated form of WNT5A that is produced and secreted exclusively by RANKL‐stimulated osteoclast precursors.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…WNT5A is a complex protein that not only has multiple isoforms, but that also undergoes many PTMs that dictate its cellular effects through interactions with different receptors . Our study validates and adds to the complexity of WNT5A by identifying a unique, posttranslational phosphorylated form of WNT5A that is produced and secreted exclusively by RANKL‐stimulated osteoclast precursors.…”
Section: Discussionsupporting
confidence: 61%
“…WNT5A was previously reported to undergo PTMs, which influence WNT5A secretion and affinity for frizzled receptors, as well as receptor‐specific internalization . We investigated whether osteoblast‐ and osteoclast‐produced WNT5A are modified by PTMs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports showed that Wnt5a promotes apical membrane polarization by regulating Rac and Rho activities, leading to translocation of apical marker, such as F-actin, to apical region of MDCK or IEC6 cells3940. To examine whether apical membrane polarization affected AQP2 trafficking, we co-stained the mpkCCD cells with AQP2 and F-actin after the treatment with Wnt5a.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we demonstrated that different Wnts (Wnt3a, Wnt5a, and Wnt11) and Wnt receptors (frizzled 2, frizzled 7, LRP6, ROR2, and RYK) have distinct secretory and trafficking routes in polarized MDCK epithelial cells (30,31). For instance, Wnt3a was secreted basolaterally and LRP6 was trafHere we showed that CKAP4 is a receptor for DKK1 and DKK1/CKAP4 signaling promotes normal and cancer cell proliferation through the PI3K/AKT pathway.…”
Section: Dkk1 Is Secreted Apically In Polarized Mdck Cells and Stimulmentioning
confidence: 89%